PENGARUH PERMAINAN LARI ESTAFET MODIFIKASI TERHADAP PENINGKATAN GERAK DASAR LOKOMOTOR UNTUK ANAK TUNAGRAHITA KELAS I DI SDLB N KEDUNG KANDANG KOTA MALANG - Cholil Rusman M; Sapto Adi; Saichudin Saichudin (Jurnal Sport Science, 2017)
Abstract Mental retardation refers to children who suffer from mental disorder and motorist development. If we talk about children growth, both normal children and the ones with special needs have to be able to deal with locomotors basic movement, especially sprint and jump. This research using One Group Pretest-posttest Design method, that is pre-test design before being treated, thus the treatment result can be known more accurate, because it can compare with the condition before being treated. The sample used were 6 people who were treated for eight meetings. Instruments used to determine the ability to run and jump is test on 40 meters sprint for children of mental retardation at 10-12. The result of the research is based on data analysis using the test-t repeated observation obtained test-t -2,712 with probability 0.042 <α= 0.05, which means significant.. The conclusion of this study is that there is an effect of game run relay modification toward the increase of locomotors basic movement of the one grade students with mental retardation at the inclusive elementary school (SDLB) in Kedungkandang Malang.Keywords: Game run relay, mental retardation, sprint ability.